Impact of environment on hotel customer satisfaction in Southeast Asia: A study of online booking site reviews - Ding, Cuicui; Guo, Qingran; Rehman, Alam; Zeeshan, Muhammad (Frontiers in Environmental Science, 2022)
This paper empirically analyzes the effect of the environment on hotel customer satisfaction in Southeast Asian countries, as reflected in reviews on online booking sites. The logistic regression method is applied to extract the estimations. The empirical outcomes reveal that the environment can significantly influence customer satisfaction, which means tourists are likely to maximize their satisfaction by choosing destinations that provide a good environment. In addition, room price, hotel location, and service quality can also increase customer satisfaction. Web-based customer reviews potentially affect the booking decisions of future tourists, who carefully evaluate reviewers’ comments when making decisions about accommodation. Hotel authorities in Southeast Asian countries can improve hotel service by adopting renewable energy resources, which may in turn increase the booking interest. Furthermore, customer feedback is an essential factor, and hotel authorities can improve hotel services by considering reviewers’ comments.